PENGARUH DIRECT INSTRUCTION MODEL TERHADAP KETERAMPILAN GERAKAN ROLL DEPAN PEMBELAJARAN SENAM LANTAI KELAS VII DI SMPN 3 CIKARANG UTARA - Erika Amelia; Rahmat Iqbal; Dhika Bayu Mahardhika (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The purpose of making this thesis is to determine the effect of the Direct Instruction Model on the Front Roll Movement Skills of Class VII Floor Gymnastics Learning at SMPN 3 Cikarang Utara. To answer the formulation of research problems that have been formulated, the authors use a quantitative approach with experimental methods. This research was conducted at SMPN 3 Cikarang Utara by taking one class as a research sample, namely class VII which amounted to 36 respondents out of 180 class VII students. The sample technique used in this study was purposive sampling. The form of research design uses pre-experimental design with the form of one-group pretest-posttest design. This research instrument uses a test instrument for the ability of basic techniques of floor gymnastics movements, from this study the average before treatment and after treatment has increased significantly, namely floor gymnastics increased from the mean pretest 46.72 to the mean posttest 78.69. Meanwhile, the results of the calculation of the Paired Sample T Test hypothesis testing with the data obtained from this study are a significance value (2-tailed) of 0.000 <0.05, meaning that there is a significant influence between the average score before treatment and the average score after treatment. It can be concluded that the direct instruction model can affect the learning of class VII floor gymnastics at SMPN 3 Cikarang Utara.